Pencegahan Kasus Lesbian di Lembaga Pemasyarakatan Indonesia: Pendekatan Sosial Hukum - Rachmayanthy Rachmayanthy; Muhammad Ali Equatora; Cahyoko Edi Tando (Jurnal Ilmiah Kebijakan Hukum, 2023)
The case of lesbians in Correctional Institutions is phenomenal and has already come to the attention of all groups; there are also health impacts that threaten the community's safety if Lesbians are indicated. Lesbian cases, in particular, occur not only in the community but have also penetrated Correctional Institutions (Lapas), so early prevention is needed to maintain security and order in Correctional Institutions. This study will use a Sociolegal Approach; data collection is carried out using interview techniques with prisoners. The data analysis is carried out in the form of a Sociolegal Approach with rules relevant to the topic of discussion. The result is that regulations regarding preventing Lesbians in Correctional Institutions are not found. Still, the researchers found that officers can review granting rights to each prisoner if the prisoner commits an act that disturbs conductivity in the Correctional Institutions. The imposition of a measurable sentence against the prisoner isalso enforced. The vision and mission within Correctional Institutions, which focus on coaching, have also been carried out because coaching is the right of convicts. Guidance is generally not only on the religious side but also on positive activities for self-development in line with the assessment of Community Guidance.